High‐frequency current source converter for a direct drive powertrain in a wave energy converter. Issue 17 (26th April 2019) - McDonald, Stephen P.; Baker, Nick J.; Pickert, Volker
Abstract : Wave energy converters (WECs) generally use a mechanical solution such as hydraulics or gearing to optimise the extraction of energy from the incoming waves prior to converting it into electrical energy via a high‐speed rotating generator. This simplifies the electrical power conversion system (EPCS) design and facilitates the use of mechanical energy storage such as springs, compressed air, or hydraulic accumulators. The naturally peaky nature of the WEC power can thus be reduced and there is potential to tune the resonant frequency of the WEC. The potential design of a current source converter (CSC) for an integrated low‐speed direct‐drive power take‐off (PTO) for a WEC is described here. Silicon carbide (SiC) devices which enable high switching frequencies with a beneficial reduction in passive component dimensions are considered. Issues such as fault tolerance, protection, and parasitic inductance are investigated leading to an improved layout proposal.